Gene and Phenotype Expansion of Unexplained Early Infantile Epileptic Encephalopathy - Liu, Xianyu; Shen, Qiyang; Zheng, Guo; Guo, Hu; Lu, Xiaopeng; Wang, Xiaoyu; Yang, Xiao; Cao, Zixuan; Chen, Jing (Frontiers in Neurology, 2021)
Objective: The genetic etiology of epileptic encephalopathy (EE) is growing rapidly by next generation sequencing (NGS) technique. In this single-center study, we aimed to investigate a cohort of Chinese children with early infantile epileptic encephalopathy (EIEE). Methods: NGS was performed on 50 children with unexplained EIEE. The clinical profiles of children with pathogenic variants were characterized and analysed in detail. The conservation analysis and homology modelling were to predict the impact of STXBP1 mutation on the protein structure. Results: Pathogenic variants were identified in 17 (34%) out of 50 children. Sixteen variants were de novo, and one was a compound heterozygous mutation. Gene and phenotype were broadened, and PIGN as a new candidate EIEE gene needed further functional study. The molecular mechanism of STXBP1 mutation revealed the alteration of amino acid affected the protein stability. Significance: NGS is a useful diagnostic tool, and single genes with causative de novo variants or compound heterozygous are discovered to allow for expansion of gene and phenotype in EIEE. Early recognition could lead to early diagnosis and gene intervention to offer an improved developmental outcome.